Parasite co-infections and their impact on survival of indigenous cattle - Thumbi, Samuel M.; Bronsvoort, B.M. de C.; Poole, Elizabeth J.; Kiara, Henry K.; Toye, Philip G.; Mbole-Kariuki, Mary N.; Conradie, I.; Jennings, A.; Handel, Ian G.; Coetzer, Jacobus A.W.; Steyl, J.C.A.; Hanotte, Olivier H.; et al. (Public Library of Science, 2014)
In natural populations, individuals may be infected with multiple distinct pathogens at a time. These pathogens may act independently or interact with each other and the host through various mechanisms, with resultant varying outcomes on host health and survival. To study effects of pathogens and their interactions on host survival, we followed 548 zebu cattle during their first year of life, determining their infection and clinical status every 5 weeks. Using a combination of clinical signs observed before death, laboratory diagnostic test results, gross-lesions on post-mortem examination, histo-pathology results and survival analysis statistical techniques, cause-specific aetiology for each death case were determined, and effect of co-infections in observed mortality patterns. East Coast fever (ECF) caused by protozoan parasiteTheileria parva and haemonchosis were the most important diseases associated with calf mortality, together accounting for over half (52%) of all deaths due to infectious diseases. Co-infection with Trypanosoma species increased the hazard for ECF death by 6 times (1.4–25; 95% CI). In addition, the hazard for ECF death was increased in the presence of Strongyleeggs, and this was burden dependent. An increase by 1000 Strongyle eggs per gram of faeces count was associated with a 1.5 times (1.4–1.6; 95% CI) increase in the hazard for ECF mortality. Deaths due to haemonchosis were burden dependent, with a 70% increase in hazard for death for every increase in strongyle eggs per gram count of 1000. These findings have important implications for disease control strategies, suggesting a need to consider co-infections in epidemiological studies as opposed to single-pathogen focus, and benefits of an integrated approach to helminths and East Coast fever disease control.